Evolution of genes associated with gynoecium patterning and fruit development in Solanaceae (2018)
ABSTRACT: Background and Aims The genetic basis of fruit development has been extensively studied in Arabidopsis, where major transcription factors controlling valve identity (i.e. FRUITFULL), replum development (i.e. REPLUMLESS) and the differentiation of the dehiscence zones (i.e. SHATTERPROOF, INDEHISCENT and ALCATRAZ) have been identified. This gene regulatory network in other flowering plants is influenced by duplication events during angiosperm diversification. Here we aim to characterize candidate fruit development genes in the Solanaceae and compare them with those of Brassicaceae. • Methods ALC/SPT, HEC/IND, RPL and AG/SHP homologues were isolated from publicly available databases and from our own transcriptomes of Brunfelsia australis and Streptosolen jamesonii. Maximum likelihood phylogenetic analyses were performed for each of the gene lineages. Shifts in protein motifs, as well as expression patterns of all identified homologues, are shown in dissected floral organs and fruits in different developmental stages of four Solanaceae species exhibiting different fruit types. • Key Results Each gene lineage has undergone different duplication time-points, resulting in very different genetic complements in the Solanaceae when compared with the Brassicaceae. In general, Solanaceae species have more copies of HEC1/2 and RPL than Brassicaceae, have fewer copies of SHP and the same number of copies of AG, ALC and SPT. Solanaceae lack IND orthologues, but have pre-duplication HEC3 homologues. The expression analyses showed opposite expression of SPT and ALC orthologues between dry- and fleshy-fruited species during fruit maturation. Fleshy-fruited species turn off RPL and SPT orthologues during maturation. • Conclusions The gynoecium patterning and fruit developmental genetic network in the Brassicaceae cannot be directly extrapolated to the Solanaceae. In Solanaceae ALC, SPT and RPL contribute differently to maturation of dry dehiscent and fleshy fruits, whereas HEC genes are not generally expressed in the gynoecium. RPL genes have broader expression patterns than expected.